Etiology-specific assessment of predictors of long-term survival in chronic systolic heart failure. (1st June 2015) - Franke, Jennifer; Zugck, Christian; Hochadel, Matthias; Hack, Anna; Frankenstein, Lutz; Zhao, Jingting Désirée; Ehlermann, Philipp; Nelles, Manfred; Zeymer, Uwe; Winkler, Ralph; Zahn, Ralf; Katus, Hugo A.; et al.
Abstract: Background: We sought to identify prognostic factors of long-term mortality, specific for the underlying etiology of chronic systolic heart failure (CHF). Methods and results: Between 1995 and 2009 baseline characteristics, treatment and follow-up data from 2318 CHF-patients due to ischemic (ICM; 1100 patients) or dilated cardiomyopathy (DCM; 1218 patients) were prospectively compared. To calculate hazard ratios with 95%-confidence intervals cox regression was used. We respectively established etiology-specific multivariable models of independent prognostic factors. During the follow-up period of up to 14.8 years (mean = 53.1 ± 43.5 months; 10, 264 patient-years) 991 deaths (42.8%) occurred. In the ICM-cohort, 5-year-survival was 53.4% (95% CI: 49.9–56.7%), whereas in DCM-patients it was higher (68.1% (95% CI: 65.1–71.0%)). Age, ejection fraction, or hyponatremia were independent predictors for mortality in both cohorts, whereas diabetes, COPD, atrial fibrillation and a heart rate of ≥ 80/min carried independent predictive power only in ICM-patients. Conclusion: This study demonstrates the disparity of prognostic value of clinically derived risk factors between the two main causes of CHF. The effects of covariables in DCM-patients were lower, suggesting a less modifiable disease through risk factors considering mortality risk. An etiology-specific prognostic model may improve accuracy of survival estimations in CHF.